Life Support in High Age: Northern Norway 1865-1900 - Elstad, Ingunn (Journal of Family History, 2013)
This article explores how very old people in Northern Norway supported life before economic modernization, from nineteenth-century census registrations and ethnographic sources. Very few lived alone. About 80 percent were primarily supported by living with relations—family, kin, or nonkin, participating with work and experience, the majority through a retirement agreement. In the northernmost parts, where Sámi traditions of land ownership dominated, retirement was uncommon. Other very old supported life from independent work or public relief. Old women with few ties were at particular risk of destitution.